A randomized, placebo-controlled trial of the BTK inhibitor zanubrutinib in hospitalized patients with COVID-19 respiratory distress: immune biomarker and clinical findings - Treon, Steven P.; Kotton, Camille N.; Park, David J.; Moranzoni, Giorgia; Lemvigh, Camilla K.; Gathe, Joseph C.; Varughese, Tilly A.; Barnett, Christopher F.; Belenchia, Johnny M.; Clark, Nina M.; Farber, Charles M.; Abid, Muhammad Bilal; et al. (Frontiers in Immunology, 2025)
BackgroundCytokine release triggered by a hyperactive immune response is thought to contribute to severe acute respiratory syndrome coronavirus 2019 (SARS-CoV-2)–related respiratory failure. Bruton tyrosine kinase (BTK) is involved in innate immunity, and BTK inhibitors block cytokine release. We assessed the next-generation BTK inhibitor zanubrutinib in SARS-CoV-2–infected patients with respiratory distress.MethodCohort 1 had a prospective, randomized, double-blind, placebo-controlled design; cohort 2 had a single-arm design. Adults with SARS-CoV-2 requiring hospitalization (without mechanical ventilation) were randomized in cohort 1. Those on mechanical ventilation ≤24 hours were enrolled in cohort 2. Patients were randomized 1:1 to zanubrutinib 320 mg once daily or placebo (cohort 1), or received zanubrutinib 320 mg once daily (cohort 2). Co-primary endpoints were respiratory failure-free survival rate and time to return to breathing room air at 28 days. Corollary studies to assess zanubrutinib’s impact on immune response were performed.ResultsSixty-three patients in cohort 1 received zanubrutinib (n=30) or placebo (n=33), with median treatment duration of 8.5 and 7.0 days, respectively. The median treatment duration in cohort 2 (n=4) was 13 days; all discontinued treatment early. In cohort 1, respiratory failure-free survival and the estimated rates of not returning to breathing room air by day 28 were not significantly different between treatments. Importantly, serological response to coronavirus disease 2019 (COVID-19) was not impacted by zanubrutinib. Lower levels of granulocyte colony-stimulating factor, interleukin (IL)-10, monocyte chemoattractant protein-1, IL-4, and IL-13 were observed in zanubrutinib-treated patients. Moreover, single-cell transcriptome analysis showed significant downregulation of inflammatory mediators (IL-6, IL-8, macrophage colony-stimulating factor, macrophage inflammatory protein-1α, IL-1β) and signaling pathways (JAK1, STAT3, TYK2), and activation of gamma-delta T cells in zanubrutinib-treated patients.ConclusionsMarked reduction in inflammatory signaling with preserved SARS-CoV-2 serological response was observed in hospitalized patients with COVID-19 respiratory distress receiving zanubrutinib. Despite these immunological findings, zanubrutinib did not show improvement over placebo in clinical recovery from respiratory distress. Concurrent administration of steroids and antiviral therapy to most patients may have contributed to these results. Investigation of zanubrutinib may be warranted in other settings where cytokine release and immune cell exhaustion are important.Clinical Trial Registrationhttps://www.clinicaltrials.gov/study/NCT04382586, identifier NCT04382586.